2017
DOI: 10.4103/0366-6999.213963
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Posttranslational Core Fucosylation Ameliorates Rat Peritoneal Mesothelial Cell Epithelial-Mesenchymal Transition

Abstract: Background:Core fucosylation (CF), catalyzed by α-1,6 fucosyltransferase (Fut8) in mammals, plays an important role in pathological processes through posttranslational modification of key signaling receptor proteins, including transforming growth factor (TGF)-β receptors and platelet-derived growth factor (PDGF) receptors. However, its effect on peritoneal fibrosis is unknown. Here, we investigated its influence on epithelial-mesenchymal transition (EMT) of rat peritoneal mesothelial cells (PMCs) in vitro indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Our recent study has shown that blocking core fucosylation could ameliorate the rat peritoneal mesothelial cell epithelialmesenchymal transition induced by a high glucose solution in vitro. 30 Thus, in this study, we further detected the expression of core fucosylation in the peritoneal membrane of rats with peritoneal fibrosis. We then investigated the effects of inhibiting core fucosylation on the development and progression of peritoneal fibrosis, and finally compared the protective effects of core fucosylation inhibition with imatinib (an available selective PDGF receptor inhibitor).…”
mentioning
confidence: 83%
“…Our recent study has shown that blocking core fucosylation could ameliorate the rat peritoneal mesothelial cell epithelialmesenchymal transition induced by a high glucose solution in vitro. 30 Thus, in this study, we further detected the expression of core fucosylation in the peritoneal membrane of rats with peritoneal fibrosis. We then investigated the effects of inhibiting core fucosylation on the development and progression of peritoneal fibrosis, and finally compared the protective effects of core fucosylation inhibition with imatinib (an available selective PDGF receptor inhibitor).…”
mentioning
confidence: 83%
“…In the latter, FUT8 activated the β-catenin/LEF-1 transcription factor [43], while it was inhibited by miR-198-5p overexpression, resulting in EMT inhibition [44]. FUT8 promoted EMT through core fucosylation of TGF-β receptor in both breast cancer cells [45] and in rat peritoneal mesothelial cells [46]. In the former, FUT8 could be activated by the opioid analgesic fentanyl and promoted EMT and malignancy through the β-catenin pathway [47].…”
Section: Core Fucosylationmentioning
confidence: 99%
“…Galunisertib monotherapy effectively inhibited tumor growth in a number of human cancer xenografts, and was synergistic with 5-FU and paclitaxel in in vitro gastric cancer cell studies, and with sorafenib in HCC cell lines [141][142][143][144][145]. The inhibition of core fucosylation of Activin receptor-like kinase-5 (ALK-5), TBRII and PDGF receptor by Fut8 small interfering RNA (siRNA) successfully suppresses the activation of TGF-β1/ALK-5/SMAD2/3 and PDGF/ERK signaling pathways and attenuates rat PMC EMT in vitro [146]. This has important implications for the control of GDP/AGE induced CAPD EPS, but also glycosylation related renal interstitial fibrosis and carcinogenesis [132,[147][148][149].…”
Section: Targeting the Tgf-β1 Pathwaymentioning
confidence: 99%